A study of intention to leave among nurses in Malaysian public hospitals - Khatijah Omar (Kedah: Universiti Utara Malaysia, 2013)
The study focused on permanent nurses working in public hospitals in Peninsular Malaysia. Results of analysis in this study supported that job satisfaction and organizational commitment were significantly and negatively related to intention to leave while turnover opportunity was significantly and positively related to intention to leave of nurses working on permanent basis in Peninsular Malaysia.